Twenty Years of Experience in Service-Learning at The Ohio State University College of Medicine - Douglas M. Post; Firuzan Sari Kundt; Eileen Mehl; William A. Hudson; Linda C. Stone; Franklin R. Banks (The University of Alabama, 2022)
Research at Ohio State shows that service-learning curricula can improve health care, give back to the community, and help medical students grow personally and professionally.